Sistem Informasi Pengelolaan Perkebunan Kelapa Sawit Berbasis Web GIS - Faisal Akmal; Fatwa Ramdani; Aryo Pinandito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Fertilization is one way to increase palm oil production. With such a crucial role, then an efficient usage of fertilizer could cut down production cost significantly. In order to ensure an efficient fertilization, a thorough analysis on plant's fertilizer needs along with looking after harvest results. Area analysis is possibly done by utilizing WebGIS-based GIS software which is easy to operate using precision farming approach in order to run in a long term. First step is to visualize palm oil plantation using processed image data in order to supervise, analyze, and plantation and ensure continuous production. Next, determining attribute data to analyze the need of fertilizer and match it with palm oil plant fertilization age table. It is expected that the result of this research could be of help for companies to know plant's exact and proper need of fertilizer in order to save cost and continuous increase in production that will meet harvest dates.